Comparison of Soluble Dietary Fibers Extracted from Ten Traditional Legumes: Physicochemical Properties and Biological Functions - Dingtao Wu; Jiajia Wan; Wenxing Li; Jie Li; Wang Guo; Xiaoqin Zheng; Ren-You Gan; Yichen Hu; Liang Zou (Foods, 2023)
Soluble dietary fibers (SDFs) exist as the major bioactive components in legumes, which exhibit various biological functions. To improve the potential applications of legume SDFs as healthy value-added products in the functional food industry, the physicochemical properties and biological functions of SDFs from ten selected traditional legumes, including mung bean, adzuki bean, red bean, red sword bean, black bean, red kidney bean, speckled kidney bean, common bean, white hyacinth bean, and pea, were studied and compared. Results showed that the physicochemical properties of SDFs varied in different species of legumes. All legume SDFs almost consisted of complex polysaccharides, which were rich in pectic-polysaccharides, e.g., homogalacturonan (HG) and rhamnogalacturonan I (RG I) domains. In addition, hemicelluloses, such as arabinoxylan, xyloglucan, and galactomannan, existed in almost all legume SDFs, and a large number of galactomannans existed in SDFs from black beans. Furthermore, all legume SDFs exhibited potential antioxidant, antiglycation, immunostimulatory, and prebiotic effects, and their biological functions differed relative to their chemical structures. The findings can help reveal the physicochemical and biological properties of different legume SDFs, which can also provide some insights into the further development of legume SDFs as functional food ingredients.